(untitled) (Bangladesh Medical Journal, 2014)
Severe traumatic brain injury is common in all developing countries like Bangladesh. These patients are commonly managed conservatively in the most of the hospitals of our country where immediate surgical intervention and perioperative ICU facilities are not available.This cross sectional interventional study was aimed at evaluating and comparing the post operative surgical outcome of decompressive craniectomy in patients with severe traumatic brain injury (TBI) with conservatively treated patients.This study was done in Dhaka Medical College Hospital from January 2010 to December 2012. Twenty clinically suspected patients who sustained severe head injury with a GCS of 3-8 with neurological deterioration and evidence of brain contusion, laceration or evidence of brain swelling on CT Scan were included. Patient with primary fatal brain stem injury, an initial and persisting GCS score of 3, or bilaterally dilated and fixed pupil are not candidate for operative management. Outcome was assessed by Glasgow outcome scale (GOS). Follow up was given for a period of six to twelve months. DOI: http://dx.doi.org/10.3329/bmj.v43i2.21392 Bangladesh Med J. 2014 May; 43 (2): 100-102